ANALISIS WEBSITE JDIH PROVINSI SUMATERA SELATAN DALAM MEMBERIKAN INFORMASI MENGGUNAKAN GOOGLE ANALYTICS - Oktariansyah, Oktariansyah; Negara, Edi Surya; Herdiansyah, M. Izman; Kurniawan, Tri Basuki; Saksono, Prihambodo Hendro (Jurnal Teknologi Informasi Mura, 2024)
The development of information technology has had a major impact on human life, allowing us to receive information quickly. The JDIH website is one of the efforts to provide digital-based information through a website platform that can be accessed quickly to provide information to improve efficiency, accessibility and convenience in providing public services to the people of South Sumatra Province to realize good governance. The purpose of this study is to measure the performance of the JDIH website (Legal Documentation and Information Network) in providing information services to the public. The purpose of this analysis is to evaluate the JDIH Website using Google Analytics Tools to understand the characteristics and statistics of its visitors. The results of the research and analysis that have been carried out by taking JDIH website data with the Google Analytics Algorithm within 28 days have had 2,445 views with an engagement ratio of 61.51%, visitor traffic data from organic search was also obtained, the largest number of which was 628 visitors from Google, Bing, Yahoo. The visitor operating system to access the website uses Windows as many as 418, Android 250, and iOS 47. The largest number of JDIH Website visitors is from Palembang City, which is 382 visitors.